The dual probiotic and antibiotic nature of Bdellovibrio bacteriovorus - Mohammed Dwidar; Ajay Kalanjana Monnappa; Robert J. Mitchell (BMB Reports, 2012)
Bdellovibrio bacteriovorus is a predatory bacterium which attacksand consumes other bacterial strains, including the wellknown pathogens E. coli O157：H7, Salmonella typhimuriumand Helicobacter pylori. This remarkable activity has been thefocus of research for nearly five decades, with exciting practicalapplications to medical, agriculture and farming practicesrecently being published. This article reviews many of the excitingsteps research into this bacterium, and similar bacteria,has taken, focusing primarily on their use as both an antibioticto remove harmful and pathogenic bacteria and as a probioticto help curb and control the bacterial populations within theintestinal tract. Owing to the unique and dual nature of thisbacterium, this review proposes the use of “amphibiotic” todescribe these bacteria and their activities. [BMB reports 2012;45(2): 71-78]